Sympathetic Crashing Acute Pulmonary Edema in a Postoperative Case of Pituitary Macroadenoma - Varun Jain; Swati Singh; Ruchinder Kaur; Rahul Gupta (Journal of Neuroanaesthesiology and Critical Care)
We present a case of 58-year-old male operated for pituitary macroadenoma. On the 7th postoperative day, the patient developed sudden-onset breathlessness and desaturation needing ventilatory support. His cardiac function, which was normal preoperatively, deteriorated (ejection fraction 20%) but cardiac enzyme levels were normal. Chest X-ray was suggestive of pulmonary edema. His condition stabilized with the use of noninvasive mechanical ventilation, high-dose nitroglycerine (NTG) infusion, and furosemide over the next 12 hours. Cardiac functions improved to baseline after about a week.